PENGARUH PER, STRUKTUR MODAL ,IOS DAN LIKUIDITAS TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI TAHUN 2015-2017 - Febrina Hary Putri, 14.05.52.0089; Indarti, MG. Kentris (Students' Journal of Accounting and Banking, 2019)
The purpose of study is to know influence PER, Capital Structure, Investement Opportunity Set and Liqudity against the value of the company. As for thepopulation in this study the population used in this study is a manufacturing company listed on the Indonesia stock exchange (BEI) in 2015-2017. The sample in this study was chosen using purposive sampling method,namely how to randomly draw or select samples that have a specific goal or target. The analytical tool used is multiple linear regresssion . Secondary data in this study are prospects of manufacturing companies listed on the indonesia stock exchange(BEI) in 2015-2017. Sorce of financial statement data obtained from IDX.Research results show that PER, Capital Structure, Liqudity affect the value of the company while Investement Opportunity Set does not affect the value of the company.This study was sampled only for companies in the manufacturing sectorhence it is possible to expand researched sectors such as the financial sector,property, transportation, and service companies so that they can provide better and more accurate result.